Bayesian data-driven framework for structural health monitoring of composite structures under limited experimental data - Ferreira, Leonardo de Paula S.; Teloli, Rafael de O.; da Silva, Samuel [UNESP]; Figueiredo, Eloi; Maia, Nuno; Cimini, Carlos A. (SAGE Publications, 2024)
Ultrasonic-guided waves can be used to monitor the health of thin-walled structures. However, the run of experimental damage tests on materials like carbon fiber-reinforced plastics can be impractical and costly. Instead, numerical models can be used to create hybrid datasets to train machine learning algorithms, integrating data from numerical and experimental tests. This paper presents a Bayesian-driven framework to compensate for limited experimental data regarding Lamb wave propagation in composite plates. Using Bayesian inference, the framework updates a numerical finite element model, considering observed uncertainties by sampling posterior probability density functions for input parameters using Markov–Chain Monte Carlo simulations with the Metropolis-Hastings algorithm. A neural network surrogate model speeds-up these simulations, leading to a model that replicates the uncertain experimental setup. This model then generates data to augment true experimental data. Finally, a one-dimensional convolutional neural network is trained on a three different datasets to analyze Lamb wave signals and assess damage. Comparing training strategies shows the hybrid dataset augmented by samples generated by the updated FE model gives the most accurate damage size predictions.
Keywords: Bayesian calibration; composite materials; convolutional neural networks; machine learning; Structural health monitoring